2020
DOI: 10.2478/hukin-2020-0045
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Measures of Functional and Isometric Lower Body Strength, Aerobic Capacity, Anaerobic Power, Sprint and Countermovement Jump Performance in Professional Soccer Players

Abstract: The purpose of this study was to assess a wide range of physiological and performance variables and investigate whether and to what extent these variables are associated with each other in soccer. Twenty-five male soccer players (25.1 ± 4.56 years; body mass, 75.2 ± 5.92 kg; body height, 180.6 ± 5.45 cm) performed: 5- and 30-m sprints (T5m and T30m, respectively), 1-repetition-maximum (1RM) half squat, maximal voluntary isometric contraction (MVIC) of the knee extensors, countermovement jump (CMJ) to obtain ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 47 publications
5
35
2
1
Order By: Relevance
“…The best predictor of P peak was body mass highlighting the relationship of muscle power with human size ( Bahenský et al, 2020 ; Taketomi et al, 2021 ). Previously, it was shown that rP peak was related with 5 m, 30 m sprint times, maximal voluntary isometric contraction of the knee extensors, half squat repetition maximal and countermovement jump height in soccer players ( Boraczyński et al, 2020 ), performance of short and maximal effort that might be evaluated by the F-v test. Comparing the prediction models of P peak and rP eak, it was observed that the coefficient of determination was higher for the absolute than for the relatively score of peak power.…”
Section: Discussionmentioning
confidence: 99%
“…The best predictor of P peak was body mass highlighting the relationship of muscle power with human size ( Bahenský et al, 2020 ; Taketomi et al, 2021 ). Previously, it was shown that rP peak was related with 5 m, 30 m sprint times, maximal voluntary isometric contraction of the knee extensors, half squat repetition maximal and countermovement jump height in soccer players ( Boraczyński et al, 2020 ), performance of short and maximal effort that might be evaluated by the F-v test. Comparing the prediction models of P peak and rP eak, it was observed that the coefficient of determination was higher for the absolute than for the relatively score of peak power.…”
Section: Discussionmentioning
confidence: 99%
“…One particular movement, the CMJ, may be beneficial for incorporation with FP and mMoCap testing as it has been used widely as a screening and readiness measure for athletes and military personnel as it is directly correlated to isometric strength, one repetition maximum half squat ( Boraczyński et al, 2020 ), and is reliable and repeatable for quantifying neuromuscular readiness ( Cormack et al, 2008 ; Welsh et al, 2008 ; Merrigan et al, 2020 ). The CMJ is a simple and field-ready test that may provide information regarding MSKI risk and preventative strategies to mitigate MSKIs through information, such as force production, loading kinematics via FP or mMoCap technology ( Hart et al, 2019 ; Pontillo and Sennett, 2019 ; Pontillo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Soccer, due to its requirements of covering up to 12 000 m in a game, frequent changes of direction and a multitude of various incidents (including fouls), seems to significantly increase the risk of foot injuries, including fractures among players ( Boraczyński et al, 2020 ). The player's position on the field has to be considered in this regard ( Thomson et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%